Novel Insights into miRNA Regulation of Storage Protein Biosynthesis during Wheat Caryopsis Development under Drought Stress - Chen, Xin-yu; Yang, Yang; Ran, Li-ping; Dong, Zhao-di; Zhang, Er-jin; Yu, Xu-run; Xiong, Fei (Frontiers in Plant Science, 2017)
Drought stress is a significant abiotic stress factor that affects wheat yield and quality. MicroRNA (miRNA) plays an important role in regulating caryopsis development in response to drought stress. However, little is known about the expression characteristics of miRNAs and how they regulate protein accumulation in wheat caryopsis under drought stress. To address this, two small RNA libraries of wheat caryopsis under control and drought stress conditions were constructed and sequenced. A total of 125 miRNAs were identified in the two samples, of which 110 were known and 15 were novel. A total of 1981 miRNA target genes were predicted and functional annotations were obtained from various databases for 1641 of them. Four miRNAs were identified as differentially expressed under drought stress, and the expression patterns of three of them were consistent with results obtained by reverse transcription polymerase chain reaction (RT-PCR) and reverse transcription quantitative polymerase chain reaction (RT-qPCR). Moreover, three miRNA-target pairs showed negative regulation tendency, as revealed by RT-qPCR. Functional enrichment and pathway analysis revealed that four pathways may be involved in storage protein biosynthesis. Furthermore, drought stress significantly increased the accumulation of protein bodies and protein content in wheat endosperm. In summary, our findings suggest that drought stress may enhance storage protein by regulating the expression of miRNAs and its target genes.